Tomographic image reconstruction of monitoring flaws on gas pipeline based on reverse ultrasonic tomography - Idroas, Mariani (IEEE Computer Society, 2014)
The capability of a technique to reconstruct a tomographic image of flaws existence on gas pipeline via reverse ultrasonic tomography is presented. The ultrasonic tomography system is developed to monitor flaws circumferentially on pipeline with contactless measurement of distance from sensors to the pipe. In oil and gas industry, the applications of ultrasonic tomography technique for flaw detection in pipeline are limited as this technology is still in its infancy. The design of the ultrasonic tomography system consists of ultrasonic sensing system, data acquisition and image reconstruction system. A reflection mode of ultrasonic sensor is used where the output ultrasonic signal reflected from the pipe to the sensor is acquired. The collected data will be used in image reconstruction system to visualize the image. In image reconstruction process, a linear back projection algorithm is used in order to reconstruct the image of the pipe profile with flaws existence. The back projection algorithm is derived by the mathematical relationship of forward and inverse problem. This reconstruction algorithm is implemented in Matlab software to analyze the performance of the technique for different projection and arrays. Through the simulated result, the reconstructed image based on four projections is found to be less smeared compared to the image based on two projections. The effect of aliasing on the image is also reduced as the number of projection is increased. Several images of pipe with flaws existence are reconstructed based on four projections, with 7 × 7 arrays of pixels and twenty-eight of ultrasonic sensors.